Potential Health Implications of Heavy Metal Contamination of Streams Near Quarry Sites in Akamkpa, Cross River State, Nigeria - Atsa, Joy William Undie; Uzochukwu, Ugochukwu Cornelius; Madu, Christian Ndubuisi; Obiefuna, Josiah N.; Onuoha, Edwin; Kanu, Hannah Izuakolam; Moses, Moses Kishaleunim; Ayinzat , Obed; Igelle, Idaga Evaristus (Studia Ecologiae et Bioethicae, 2026)
This study examined the potential health implications of heavy metal contamination of streams near quarry sites in Akamkpa, Cross River State. Three rural communities were selected (Awi, Nsan, Old Netim) and three streams near operating quarries were sampled. 216 water samples were analysed for 15 parameters (temperature, pH, colour, turbidity, TSS, TDS, EC, Total hardness, DO, BOD, COD, CI, NOS, SO4, HCO3-), 7 heavy metals (Pb, Cu, Cr, Zn, Cd, Ni, Ba) and 2 microbiological parameters (Total Coliform, E-Coli). Samples were collected between April 2023 and June 2024, during 2 wet and 2 dry seasons. Atomic Absorption Spectrophotometer (AAS) was used for testing heavy metals. Results from the laboratory analyses were tested for differentials using ANOVA. Nemerow Pollution Index was applied to assess the overall pollution status of these streams. The potential health burden was determined using Hazard Index (HI) and Risk Index (RI) models. Results showed that RI for children was greater than 10-6 threshold value in stream 1 and 3. HI values for children and adults were insignificant. Stream 1 had heavy metal values that were significantly higher than stream 2 and 3 for all parameters. Zn posed a significantly higher health risk in stream 1 than in stream 2 and 3. Cd in stream 3 was above permissible limits. Stream 3 was the most polluted posing carcinogenic health risk due to Cd exposure, while water from stream 2 was not polluted and suitable for drinking. Regular monitoring for stream 1 and 3 is advised as the Zn and Cd levels in the two streams exceeded permissible limits. Other